The Flavin-Containing Reductase Domain of Cytochrome P450 BM3 Acts as a Surrogate for Mammalian NADPH-P450 Reductase - Park, Seon-Ha (The Korean Society of Applied Pharmacology, 2012)
Cytochrome P450 BM3 (CYP102A1) from Bacillus megaterium is a self-sufficient monooxygenase that consists of a heme domain and FAD/FMN-containing reductase domain (BMR). In this report, the reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) by BMR was evaluated as a method for monitoring BMR activity. The electron transfer proceeds from NADPH to BMR and then to BMR substrates, MTT and CTC. MTT and CTC are monotetrazolium salts that form formazans upon reduction. The reduction of MTT and CTC followed classical Michaelis-Menten kinetics (k(cat)=4120 min(−1), K(m)=77 μM for MTT and k(cat)=6580 min(−1), K(m)=51 μM for CTC). Our continuous assay using MTT and CTC allows the simple, rapid measurement of BMR activity. The BMR was able to metabolize mitomycin C and doxorubicin, which are anticancer drug substrates for CPR, producing the same metabolites as those produced by CPR. Moreover, the BMR was able to interact with CYP1A2 and transfer electrons to promote the oxidation reactions of substrates by CYP1A2 and CYP2E1 in humans. The results of this study suggest the possibility of the utilization of BMR as a surrogate for mammalian CPR.